Being successful aged at one hundred years old: alternative and subjective criteria - Araújo, Lia (2019)
Age, i.e. being younger, has been the most consistent predictor of successful aging, indicating a dramatic drop of the rate of success with advancing age. However, emergent studies based on expanded psychological concepts have been revealing the admirable capacity of oldest old individuals to overcome adversities and adapting to the challenges of very advanced age. This study aims to explore alternative criteria to Rowe and Kahn successful aging model in centenarians. A sample of 70 individuals (Mage100.91, SD 1.37, 87.1%female) with cognitive capacity for answering self-report questions were selected from the population-based Oporto Centenarian Study (PT100). Perceived economic status, sub- jective health and happiness were considered as components to assess successful aging. Main findings revealed that 62.9% of the sample was able to meet economic needs, 44.3% was happy and 32.3% reported a positive self-perception of health. 12.9% of the participants satisfied all three criteria and 16.1% didnt fulfilled any. A previous study using the same alternative criteria found that 47.5% of centenarians were successful aged, whereas none of them satisfied all three objective components from Rowe and Kahn’s success- ful aging model (Cho et al., 2012). Thus, the higher propor- tion of centenarians with positive self-ratings demonstrate that they may feel successful despite not being objectively considered as so. The alternative criteria of perceived eco- nomic status, subjective health and happiness considered in this study seem to be suitable to approach successful aging in very advanced age.